Ionospheric induced plasma disturbances afore the m7.9 eastern Sichuan china earthquake of 12th may, 2008 - E. Thomas, Jewel; J. George, Nyakno; M. Ekanem, Aniekan; E. Ekpenyong, Nsikak (International Journal of Advanced Geosciences, 2019)
A great number of earthquakes occur yearly in different areas and almost 100 -120 of them have a magnitude above 5. These seismic activities are very harmful for the inhabitants. Findings reveal that this seismo-electro-magnetic abnormality is a mirror image of some processes, which originated a few weeks before the main event and stay until few days after it. Plasma ion analyser (IAP) and Instrument Sonde de Langmuir (ISL) sensors) experiments available on Detection of Electromagnetic Emissions Transmitted from Earthquake Regions (DEMETER) and Total Electron Content (TEC) from Global Positioning System (GPS) satellites, were employed to study the variations of electron and ion density for ionospheric disturbances before the M7.9 Eastern Sichuan China earthquake of 12th May, 2008. The study revealed seismo-ionospheric induced perturbations exactly three weeks afore the earthquake in all four investigated parameters. Electron density recorded 16.94 cm-3, electron temperature revealed - 2.25 o C while total ion density displayed 6.57 cm-1. The total electron content ranged from 4.28 to 3.6. The disturbance storm time (Dst) and planetary 3-hourly range (Kp) indices were used to classify pre-earthquake anomalies from the other anomalies associated with geomagnetic activities and was seen that this day (-21days relative to the earthquake) was devoid of geomagnetic storm, thus the observed perturbations were seismo-induced but not geomagnetic induced.Â Â Â